Biomolecular Protective Effects of Bacopa Monnieri (L.) Pennell Leaf Extracts Against Oxidative Damage (Bangladesh Journal of Botany, 2022)
In living systems, free radicals are constantly generated and they can cause extensive damage to tissues and biomolecules, leading to various disease conditions, especially degenerative diseases, and extensive lysis.The most effective way to eliminate free radicals which cause oxidative stress is with the help of antioxidants. Antioxidants prevent free radical-induced tissue damage by preventing the formation of radicals by scavenging them, or by promoting their decomposition. In the present study, the biomolecular protective effects of B. monnieri leaf extracts against oxidative stress induced damage to lipids and DNA in cell free systems and intact cells were analyzed. Results showed that the leaf extracts of B. monnieri rendered protection against oxidative stress induced damage in both cell-free systems and intact cells.Bangladesh J. Bot. 51(1): 123-129, 2022 (March)